2023
DOI: 10.1186/s12904-023-01175-8
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and influencing factors of nursing assistants towards hospice and palliative care nursing in chinese nursing homes: a cross-sectional study

Abstract: Background Hospice and palliative care nursing (HPCN) in China is mainly available at public primary care institutions, where nursing homes (NHs) are rarely involved. Nursing assistants (NAs) play an essential role in HPCN multidisciplinary teams, but little is known about their attitudes towards HPCN and related factors. Methods A cross-sectional study was designed to evaluate NAs’ attitudes towards HPCN with an indigenised scale in Shanghai. A to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…The findings in this study align with other studies that show a need for improvement in delivering good palliative care [ 11 – 17 , 39 ] providing continuous training and practical guidance for NAs together with RNs could improve care quality. Such training and guidance could, for example, concern factors such as ensuring patients undergo an oral assessment, assessing pain, offering an end-of-life conversation, and how to hold post-bereavement meetings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings in this study align with other studies that show a need for improvement in delivering good palliative care [ 11 – 17 , 39 ] providing continuous training and practical guidance for NAs together with RNs could improve care quality. Such training and guidance could, for example, concern factors such as ensuring patients undergo an oral assessment, assessing pain, offering an end-of-life conversation, and how to hold post-bereavement meetings.…”
Section: Discussionsupporting
confidence: 89%
“…However, several studies from different parts of the world show that there is a need for improvement for healthcare providers to be able to deliver good palliative care. One study from China shows that NAs’ attitudes to palliative care are moderate and that they need more knowledge [ 11 ] to promote high quality palliative care. A Swedish study [ 12 ] identified healthcare providers’ need for managing existential aspects of the ageing body, life and death, and engaging in existential conversations when appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Por tal razón consideramos que las competencias de los enfermeros profesionales son valiosas, indispensables y de gran importancia para poder desempeñar un óptimo servicio con eficiencia y calidad. Con estos indicadores se podrían obtener resultados que nos llevarían a realizar planes de mejora frente a este tipo de población y por ende buscar estrategias de formación para este grupo de profesionales que con lleve a beneficiar a los pacientes y familiares que estén pasando por este tipo enfermedades y a su vez al personal de salud en cuánto adquirir liderazgo en este campo, obtener reconocimiento, oportunidades en el ámbito laboral y económico (Ye et al, 2023).…”
Section: Ramírez Et Al 2023)unclassified